2005
DOI: 10.1007/s00267-003-3055-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Area Index to Retrospectively Analyze the Elimination of Fox Rabies in European Countries

Abstract: Oral vaccination of foxes (OVF) is a powerful tool to combat rabies in wildlife, and large parts of western Europe have been freed from rabies using this tool. Nevertheless, the success of OVF, given with the number of campaigns needed to eliminate the disease, depends on many factors. This article for the first time focuses on and assesses difference in OVF with respect to the spatial setting of vaccinated areas with time. The size of the areas vaccinated with time and the size of the overlapping area of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Previous research suggested that rabies could be eliminated from a region within 10–12 campaigns, i.e. 5–6 years [41,53]. But countries that successfully eliminated rabies in Europe required substantially longer (figure 3), with a median of 28 campaigns (14 years, range: 5–26) to achieve elimination, and 17 for control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research suggested that rabies could be eliminated from a region within 10–12 campaigns, i.e. 5–6 years [41,53]. But countries that successfully eliminated rabies in Europe required substantially longer (figure 3), with a median of 28 campaigns (14 years, range: 5–26) to achieve elimination, and 17 for control.…”
Section: Discussionmentioning
confidence: 99%
“…The area index captures the comprehensiveness of ORV in terms of the extent and spatial overlap of consecutive ORV campaigns [41]. Among the 22 countries area indices varied considerably from 0.006 to 1 (table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three live rabies vaccine strains used (SAG1, SAD Bern and SAD B19) in a total of 900 000 baits were reported to be ineffective as an oral prevention of rabies in wildlife (Milius et al 2004). Although ORV programs should ideally cover the entire affected area (Selhorst et al 2005), initial programs in the Baltic countries failed to vaccinate the entire affected area (Cliquet et al 2012). Specifically, initial ORV attempts in Latvia and Lithuania failed to efficiently control rabies, and were interrupted owing to budget constraints.…”
Section: Discussionmentioning
confidence: 99%